5-HT(1A) receptor binding in euthymic bipolar patients using positron emission tomography with [carbonyl-(11)C]WAY-100635. - Sargent, P; Rabiner, E; Bhagwagar, Z; Clark, L; Cowen, P; Goodwin, G; Grasby, P (2010)
BACKGROUND: This study was undertaken to examine whether brain 5-HT(1A) receptor binding is reduced in euthymic bipolar patients. METHODS: Eight medicated euthymic bipolar patients and 8 healthy volunteers underwent positron emission tomography scanning using the selective 5-HT(1A) receptor radioligand [carbonyl-(11)C]WAY-100635. RESULTS: No significant difference in global postsynaptic parametric binding potential (BP(ND)) was found between euthymic bipolar patients (mean + or - SD, 4.24 + or - 0.76) and healthy volunteers (mean + or - SD, 4.34 + or - 0.86). Ninety five percent Confidence Intervals for the difference in group mean global postsynaptic BP(ND) were -0.77 to 0.97. Analysis of regional BP(ND) did not reveal regional differences between patients and healthy controls. LIMITATIONS: The number of subjects studied was limited and all subjects were on medication. CONCLUSIONS: In contrast to previous findings of reduced 5-HT(1A) receptor binding in untreated unipolar and bipolar depressed patients [Sargent, P.A., Kjaer, K.H., Bench, C.J., Rabiner, E.A., Messa, C., Meyer, J., Gunn, R.N., Grasby, P.M., Cowen, P.J., 2000. Brain serotonin1A receptor binding measured by positron emission tomography with [(11)C]WAY-100635: effects of depression and antidepressant treatment. Arch. Gen. Psychiatry 57, 174-180]; [Drevets, W.C., Frank, E., Price, J.C., Kupfer, D.J., Holt, D., Greer, P.J., Huang, Y., Gautier, C., Mathis, C., 1999. PET imaging of serotonin1A receptor binding in depression. Biol. Psychiatry 46, 1375-1387] and in recovered unipolar depressed patients [Bhagwagar, Z., Rabiner, E.A., Sargent, P.A., Grasby, P.M., Cowen, P.J., 2004. Persistent reduction in brain serotonin1A receptor binding in recovered depressed men measured by positron emission tomography with [(11)C]WAY-100635. Mol. Psychiatry 9, 386-92], this study found no difference in 5-HT(1A) receptor BP(ND) between medicated euthymic bipolar patients and healthy controls. Normal 5-HT(1A) receptor BP(ND) in these patients may be a result of drug treatment or could indicate that reduced 5-HT(1A) receptor binding is specific to the depressed state in bipolar patients.